International Trade and Labor Market Discrimination - Julian Emami Namini; Richard Chisik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We embed a competitive search model with labor market discrimination into a two-sector two-country framework in order to analyze the relationship between international trade and labor market discrimination. Discrimination reduces the matching probability, and output, in the skilled-labor differentiated-product sector so that the country with more discriminatory firms has a comparative advantage in the simple sector. As countries alter their production mix in accordance with their comparative advantage, trade liberalization can then reinforce the negative effect of discrimination on development in the more discriminatory country and reduce its effect in the country with fewer discriminatory firms. Similarly, the relative profit difference between non-discriminatory and discriminatory firms will increase in the less discriminatory country and shrink in the more discriminatory one. In this way trade can further reduce discrimination in a country where it is less prevalent and increase it where it is more prevalent.
Keywords: F16; F66; J71; 330